KEWENANGAN PANITIA PENGAWAS PEMILIHAN UMUM DALAM PEMILIHAN KEPALA DAERAH - Yarsina, Nova (Ensiklopedia Sosial Review, 2020)
Election implementation by Panwaslu cannot play an effective role in supervising every stage of the Provincial and Regency / City Pilkada. There are obstacles faced by the District / City Panwaslu and the District Panwaslu in carrying out their roles, namely by the regulation of authority that limits all forms of Panwaslu actions in the implementation of Pilkada. The Provincial Panwaslu to the level of the Field Supervisory Committee (PPL) in the exercise of its authority will make efforts to the community such as taking action to inform people about how to exercise the authority to supervise the implementation of the Provincial and Regency / City Pilkada, so as to create an honest, fair, and regional election democratic depends on the extent to which the General Election Supervisory Committee works well and ensures the smooth running of Regional Head Elections that take place in a democratic manner.